2010
DOI: 10.1007/s13197-010-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of dietary fiber rich chicken meat patties using wheat and oat bran

Abstract: Dietary fi ber rich chicken meat patties were developed by incorporating wheat and oat bran to chicken meat at 5, 10 and 15% levels. Oat bran contained higher amount of soluble dietary fi ber (SDF) and unsaturated fatty acids (USFA) than wheat bran, whereas total dietary fi ber (TDF), insoluble dietary fi ber (IDF) and saturated fatty acids (SFA) were higher in wheat bran. Incorporation of bran signifi cantly increased the water holding capacity (WHC) and emulsion stability (ES). Oat bran showed better effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
48
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 22 publications
27
48
0
4
Order By: Relevance
“…Kilincceker and Yilmaz (2016) reported that higher frying yields were determined in fried chicken meatballs with 5% oat fibre, 5% wheat fibre, 5% pea fibre, 5% apple fibre, and 5% lemon fibre. Talukder & Sharma (2010) reported that the cooking yield of chicken meat patties prepared with wheat bran and oat bran was affected by the bran type, and the cooking yield rose as the bran content (0, 5, 10, and 15%) increased. Cava et al (2012) reported that tomato fibre (1% to 3%) reduced cooking loss in cooked chicken products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kilincceker and Yilmaz (2016) reported that higher frying yields were determined in fried chicken meatballs with 5% oat fibre, 5% wheat fibre, 5% pea fibre, 5% apple fibre, and 5% lemon fibre. Talukder & Sharma (2010) reported that the cooking yield of chicken meat patties prepared with wheat bran and oat bran was affected by the bran type, and the cooking yield rose as the bran content (0, 5, 10, and 15%) increased. Cava et al (2012) reported that tomato fibre (1% to 3%) reduced cooking loss in cooked chicken products.…”
Section: Resultsmentioning
confidence: 99%
“…However, the shelf life of meatballs and similar foods can be increased by reducing the degradation of fats and proteins. For these reasons, the use of additives, such as fibres, in preventing deterioration in meat products has been the topic of many studies (Khalil, 2000;McCarthy et al, 2001;Talukder & Sharma, 2010;Castro et al, 2011;Ibrahim et al, 2011;Cava et al, 2012;Petracci et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This was in agreement with the results observed by Yilmaz (2004) in low fat meatballs incorporated with rye bran. According to Talukder and Sharma (2010), addition of wheat and oat brans in chicken meat emulsion increased pH value with significant effect at 15 % level.…”
Section: Emulsion and Product Phmentioning
confidence: 99%
“…Dietary fibre is a key ingredient greatly used nowadays while developing nutritionally designed foods due to its significance in health promotion (Puupponen-Pimïa et al 2002) and technological impact. Some workers have made endeavour to incorporate dietary fibre, especially in some emulsion type meat products (Claus and Hunt 1991;Cofrades et al 1995;Grigelmo-Miguel et al 1999;Talukder and Sharma 2010;Kumar et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Non-meat proteins and additives play an important role in the modification of textural characteristic of meat products (Berry 1994;Gujral et al 2002;Sarıçoban et al 2009). The type and the amount of non-meat ingredients in formulations of meat products are the most important factors for product quality, technological properties and health (Talukder and Sharma 2010;Verma and Banerjee 2010).…”
Section: Introductionmentioning
confidence: 99%